A hydro - geophysical investigation of groundwater potential - RITU PREM; Shazna K; Sheeja P. S; Dr. Kurien E. K (Guide) (Tavanur 2013 Department of Land and Water Resources & Conservation Engineering)
A hydro - geophysical investigation of groundwater potential
A hydro - geophysical investigation of groundwater potential